Behavioral Aspects of Management Accounting in Supporting Innovative Managerial Decisions - Vijay Sarkar (PT. BATARI EDU CALYA, 2025)
This study investigates the behavioral dimensions of management accounting practices and their role in facilitating innovative managerial decision-making within the Indian organizational context. Management accounting has evolved beyond its traditional function of providing financial information to encompass behavioral considerations that significantly influence how managers interpret, utilize, and act upon accounting data. Drawing upon theoretical frameworks including stakeholder theory, agency theory, and upper echelons theory, this research examines the psychological, cognitive, and organizational behavioral factors that mediate the relationship between management accounting information and innovative decision outcomes. The methodology employs a mixed-methods approach combining quantitative survey data from 385 respondents across Indian manufacturing and service sector organizations with qualitative insights from semi-structured interviews with senior management accountants. Statistical analysis using SPSS reveals significant positive correlations between management accounting information utilization and decision-making effectiveness (r = 0.72, p < 0.01), with managerial risk-taking propensity and top management support serving as critical moderating variables. The findings demonstrate that behavioral factors including cognitive biases, decision styles, communication patterns, and organizational culture substantially influence how management accounting information translates into innovative decisions. The study contributes to the limited literature on behavioral management accounting in emerging economies and provides practical implications for Indian organizations seeking to leverage management accounting systems for competitive advantage through innovation.